To elucidate the mechanism of “Scrophulariae Radix–Fritillaria” in goiter by integrated metabolomics and serum pharmaco-chemistry - Chen, Lixin; Liang, Wei; Zhang, Kun; Wang, Zishuo; Cheng, Wei; Li, Wenlan (Frontiers in Pharmacology, 2024)
The pharmacodynamic substances in "Scrophulariae Radix-Fritillaria" and the molecular mechanisms underlying its therapeutic effects against goiter were analyzed through metabolomics and serum pharmaco-chemistry. A rat model of goiter was established using PTU, and the animals were treated with "Scrophulariae Radix-Fritillaria". The efficacy of the drug pair was evaluated in terms of thyroid gland histopathology and blood biochemical indices. The serum and urine samples of the rats were analyzed by UPLC-Q-TOF/MS.